“Cerberus” T Cells: A Glucocorticoid-Resistant, Multi-Pathogen Specific T Cell Product to Fight Infections in Severely Immunocompromised Patients - Koukoulias, Kiriakos; Papayanni, Penelope-Georgia; Georgakopoulou, Aphrodite; Alvanou, Maria; Laidou, Stamatia; Kouimtzidis, Anastasios; Pantazi, Chrysoula; Gkoliou, Glykeria; Vyzantiadis, Timoleon-Achilleas; Spyridonidis, Alexandros; Makris, Antonios; Chatzidimitriou, Anastasia; et al. (Frontiers in Immunology, 2021)
Adoptive immunotherapy with pathogen-specific T cells is a promising alternative to pharmacotherapy for the treatment of opportunistic infections after allogeneic hematopoietic cell transplantation or solid organ transplantation. However, clinical implementation of adoptive immunotherapy is limited to patients not receiving high-dose steroids, a prerequisite for optimal T-cell function, practically excluding the most susceptible to infections patients from the benefits of adoptive immunotherapy. To address this issue, we here rapidly generated, clinical doses of a steroid-resistant T-cell product, simultaneously targeting 4 viruses [adenovirus, cytomegalovirus, Epstein Barr virus and BK virus] and the fungus Aspergillus fumigatus, by genetic disruption of the glucocorticoid receptor (GR) gene using CRISPR/CAS9 ribonucleoprotein delivery. The product, “Cerberus” T cells (Cb-STs), was called after the monstrous three-headed dog of Greek mythology, due to its triple potential; specificity against viruses, specificity against fungi and resistance to glucocorticoids. Following efficient on-target GR disruption and minimal off-target editing, the generated Cb-STs maintained the characteristics of pentavalent-STs, their unedited counterparts, including polyclonality, memory immunophenotype, specificity and cytotoxicity while they presented functional resistance to dexamethasone. Cb-STs may become a powerful, one-time treatment for severely immunosuppressed patients under glucocorticoids who suffer from multiple, life-threatening infections post-transplant and for whom therapeutic choices are limited.